PENGUKURAN LAJU ALIRAN UDARA DALAM PIPA SECARA SIMULTAN DENGAN TRANSDUSER GANDA ULTRASONIK - Wiranata, Lalu Febrian (Universitas Mataram, 2021)
This paper aims to modification the transducer ultrasonic for measuring the distance to develop measure time of flight in the pipe with simultaneous method. To implement the application, we try to develop the microcontroller with one command transmitter and one command receiver in the same time, different from the conventional way, the transmitter and receiver work with consecutively. We try to reduce the delay time in two different transducers. In industrial, the symmetries profile must be ensured the profile always laminar. In this research, we try to use one path configuration. The result with the reference hot wire, we got the 27.76 percentage the difference of result. This is because the hot wire can measure the one path of flow in the one way of dot point.